Generation of wind power in Perlis, northern Malaysia - Nurul Razliana, Abd Razak; Mohd Irwan, Yusoff; Muhammad Irwanto, Misrun; Farhana, Z. (Institute of Electrical and Electronics Engineers (IEEE), 2013)
Link to publisher's homepage at http://ieeexplore.ieee.org